'Life is easier now': lived experience research into mentalization-based art psychotherapy. Issue 1 (3rd April 2021) - Chilvers, Samantha; Chesterman, Natalie; Lim, Alison
ABSTRACT: Background: Mentalization-based art psychotherapy (MBAP), combines mentalization-based treatment (MBT) and art therapy and is a potential intervention for people with a diagnosis of borderline personality disorder (BPD). Aims: To research the qualitative and quantitative outcomes from one 18-month outpatient MBAP programme from the perspectives of three lived experience researchers (LERs) who completed the programme. Methods: Eight people with a diagnosis of moderate to severe BPD attended an 18-month group MBAP programme. Pre- and post-therapy measures included self-report questionnaires. An additional data set was generated using AIRs for three LERs who also participated in the group. Two of the LERs also took part in a focus group to reflect on the thematic analysis of the data. Results: From the interviews, four superordinate themes were generated: (1) MBAP group experience, (2) Art as a form of communication, (3) Improved resilience and (4) Change-growth. LERs in a focus group, verified these four themes. 75% of service users were successfully discharged from secondary mental health care after completing MBAP. Conclusions: The scores in the self-report questionnaires and the successful discharge rate suggested that all programme members benefitted. Further long-term research with a larger group of LERs is needed. Implications for practice: Engagement with MBAP group therapy increased capacity to mentalize, facilitated use of artwork to manage intense emotions and aid communication in group settings. Plain-language summary: People diagnosed with borderline personality disorder commonly experience significant difficulties in interpersonal relationships and managing emotions (NICE 2009). As a result, many find everyday life highly stressful and are unable to work, study or engage in other structured activities, particularly with others. Mentalization-based art psychotherapy combines art psychotherapy with mentalization-based therapy, a verbal treatment designed for people diagnosed with borderline personality disorder. The aims of treatment are to help people learn to identify and manage their emotions and develop their capacity to reflect on themselves and the communications of others. This is achieved through a creative art-making process which takes place alongside others and reflective discussion between group members, modelled by therapists. This research explores one mentalization-based art psychotherapy programme comprising 12 weeks psychoeducation and 18 months of group therapy combined with fortnightly individual sessions. We present findings from interviews conducted with three members who we refer to as lived experience researchers (LERs). To give a sense of how effective the programme was for the majority of members we present the results from questionnaires completed pre- and post-therapy. Four major themes were identified from the interviews. Two described important ingredients in making therapy effective; group processes and art as a form of communication. Two further themes described positive changes that resulted from the treatment; increased resilience and change – growth. LERs agreed with our findings and said that art as a form of communication stood out most to them. The questionnaires' results indicated that the majority of the group no longer met the threshold for a diagnosis of borderline personality disorder following treatment. All researchers agreed on the need for further research with a larger population; however, a strength and essential part of the research process and learning was our collaboration with LERs. Abstract :